Report on national survey of exportable agricultural commodities in Nigeria, 2011/2012 - ;Consultative Committee on Agricultural Export Commodity Statistics; Nigeria; Nigeria; Central Bank of Nigeria; Nigeria; Nigeria (prepared by Consultative Committee on Agricultural Export Commodity Statistics (CCAECS), 2012)
Agriculture is the highest non-oil contributor to the National Economy, accounting for about 42 per-cent of Gross Domestic Product and generate employment for about 70 per- cent of Nigeria Population. The survey is geared towards making data available on the following cash product: Cashew, Cocoa, Coffee, Cotton, Garlic, Gum Arabic, Kola nut, Oil Palm, Rubber, Sesame seed, Shea nut, Sugarcane and Tea to Investors Researchers and Policy makers.
gp. 25/01/2019
Loans